2021
DOI: 10.4266/acc.2021.00934
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–induced acute kidney injury in critically ill patients: epidemiology, risk factors, and outcome

Abstract: Background: The kidney represents a potential target for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Acute kidney injury (AKI) can occur through several mechanisms and includes intrinsic tissue injury by direct viral invasion. Clinical data about the clinical course of AKI are lacking. We aimed to investigate the proportion, risk factors, and prognosis of AKI in critical patients affected with coronavirus disease 2019 (COVID-19).Methods: A case/control study conducted in two intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
(80 reference statements)
1
7
0
8
Order By: Relevance
“…Based on our results, no significant difference was reported between lung CT-scan and the study groups (P = 0.748). Similar to our results, in the study of Trifi et al, lung CT-scan in the group with and without AKI was not significantly different (P = 0.999) (19). In addition, in the current investigation, no correlation between the stages of AKI and the severity of lung CT-scan results was seen, indicating that variables other than the degree of pulmonary involvement contributed to the development of AKI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on our results, no significant difference was reported between lung CT-scan and the study groups (P = 0.748). Similar to our results, in the study of Trifi et al, lung CT-scan in the group with and without AKI was not significantly different (P = 0.999) (19). In addition, in the current investigation, no correlation between the stages of AKI and the severity of lung CT-scan results was seen, indicating that variables other than the degree of pulmonary involvement contributed to the development of AKI.…”
Section: Discussionsupporting
confidence: 88%
“…In the group of patients with AKI, using the mechanical ventilation was higher (P <0.001). While in the study of Trifi et al, the mechanical ventilation usage between the two groups was not significantly different (P = 0.12) (19). There was no significant difference in the mean length of ICU admission between the two groups (P = 0.211).…”
Section: Discussionmentioning
confidence: 75%
“…Some previous studies have reported that the incidence of AKI in patients with COVID-19 ranges from 7.2% to 11.5% [3,13,24]. However, other studies showed a higher AKI incidence rate of 44%-52.4% [4][5][6]. These various findings regarding AKI prevalence in patients with COVID-19 may be a result of the differences in various factors, such as disease severity, age of included patients, comorbidities, and hospital admission criteria.…”
Section: Discussionmentioning
confidence: 93%
“…Concurrently, 15 million confirmed cases of COVID-19 and 19,000 deaths due to COVID-19 are reported in the Republic of Korea [2]. Acute kidney injury (AKI) is the most common and major complication among the various complications associated with COVID-19 infection, and it has been reported to occur in approximately 10-50% of patients with COVID-19 [3][4][5][6]. AKI due to COVID-19 infection increases the risk of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation